Pretties - Westerfeld, Scott (New York Simon Pulse, 2005)
Finally surgically transformed into a "pretty," sixteen-year-old Tally, now gorgeous and programmed to think only happy thoughts, is plagued by tangled memories of living in the Smoke, a rebel colony of "ugly" runaways hiding from the Special Circumstances authorities.
Sequel: Specials.
Keywords: Beauty, Personal; Brainwashing; Science fiction